Analysis of Geotechnical Properties of Miocene Deposits of the Carpathian Foredeep = Analiza właściwości geotechnicznych utworów miceńskich zapadliska przedkarpackiego - Kokoszka, Wanda; Skrzypczak, Izabela; Wilk, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Miocene deposits of the Carpathian Foredeep are relatively poorly recognized in geotechnical terms. The article analyzes the properties of the Krakowiec clays of the Przemyśl region, in particular physical and deformation parameters. In this part of the Carpathian Foredeep, clay usually occurs at considerable depth under younger Quaternary deposits.
Keywords: Krakowiec clays; oedometer testing; soil structure; iły krakowieckie; badania edometryczne; struktura gruntu